(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Catering food service refers to the business of providing food and beverage services for various events, occasions, and gatherings. Catering services can range from small-scale, intimate affairs like birthday parties and weddings to large corporate events, conferences, and festivals. The goal of a catering service is to deliver delicious, high-quality food and drinks to clients, eliminating the need for them to cook or prepare the food themselves.